Perlawanan Rakyat Unra Terhadap Jepang di Kerajaan Bone Sulawesi Selatan - Bustan Buhari; Mr. Jumadi; La Malihu (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study reveals the resistance of the Unra people in Bone, South Sulawesi. As in other places, the villagers of Unra have long held grudges over the harsh treatment of Japanese accomplices. Even though they are also countrymen, they are more concerned with Japan than their own countrymen. The hatred of the Unra people grew because those who were appointed as Sullaluang Unra came from outside Unra. Sulaluang also acts unwisely in dealing with his people. There was hatred between the Unra community/residents and the local ruler, Sullaluang, who sided with Japan. This research uses the historical method with stages; heuristics (collecting data), Criticism (Data verification), Interpretation (data interpretation), Historiography (writing).